Elementary School Students' Metacognitive Awareness: PBL Study with HPC Strategy in Science Learning - Marleny Leasa; John Rafafy Batlolona; Jamaludin Jamaludin; Sefnath Nuniary; Venny Salhuteru (Jurnal Penelitian Pendidikan IPA, 2023)
The results of previous studies show that biological science learning for elementary school students is in the sufficient category. This is because teachers do not familiarize students with being trained in high-level thinking in the form of life skills, namely metacognitive awareness. Therefore, effective strategies are needed to increase students' metacognitive awareness. One model that can increase students' metacognitive awareness is the problem-based learning (PBL) model with the homogeneity psychocognition (HPC) strategy. The aim of the research is to analyze differences in elementary school students' metacognitive awareness in learning biological science using the PBL model, PBL with HPC strategies, and conventional models. This research used a quasi experiment with a pretest-posttest nonequivalent control group design. The number of samples participating in the research was 155 students where sampling was carried out randomly. The instrument used was the metacognitive awareness inventory which was adapted from the Junior Metacognitive Inventory (Jr. MAI) by Sperling et al (2002). The inventory consists of 18 questions with 9 items each on the aspects of knowledge of cognition and regulation of cognition. The research results found that there were significant differences in metacognitive awareness in the PBL learning model, PBL with HPC strategies compared to conventional learning. This research recommends that teachers can optimize PBL, as well as PBL with HPC strategies in increasing students' metacognitive awareness.